Propuesta urbana de renovación y revitalización en el barrio el triangulo triangulo de la ciudad de Neiva (2022)
The present research consists of analyzing and diagnosing the problems present in the neighborhood "the triangle" in Neiva-Huila, since its structuring systems suffer from deterioration and segregation, therefore, strategies are generated through urban and architectural revitalization that seeks to recover the social, ecological and urban identity. It is a process that will start from a contextual and theoretical research, which will be able to collect useful and truthful information through agreements, , development plans, supporting documents, being a reference to address during the development process, in this way, apply concepts and strategies to achieve the objectives, generate results and project an adequate proposal based not only on the regulations of the area, but also on the principles of urbanism focused on the population, such as sustainability, quality, safety and versatility, in such a way that it benefits the sector and the user.